Experimental whole‐stream warming alters community size structure. (14th December 2016) - Nelson, Daniel; Benstead, Jonathan P.; Huryn, Alexander D.; Cross, Wyatt F.; Hood, James M.; Johnson, Philip W.; Junker, James R.; Gíslason, Gísli M.; Ólafsson, Jón S.
Abstract: How ecological communities respond to predicted increases in temperature will determine the extent to which Earth's biodiversity and ecosystem functioning can be maintained into a warmer future. Warming is predicted to alter the structure of natural communities, but robust tests of such predictions require appropriate large‐scale manipulations of intact, natural habitat that is open to dispersal processes via exchange with regional species pools. Here, we report results of a two‐year whole‐stream warming experiment that shifted invertebrate assemblage structure via unanticipated mechanisms, while still conforming to community‐level metabolic theory. While warming by 3.8 °C decreased invertebrate abundance in the experimental stream by 60% relative to a reference stream, total invertebrate biomass was unchanged. Associated shifts in invertebrate assemblage structure were driven by the arrival of new taxa and a higher proportion of large, warm‐adapted species (i.e., snails and predatory dipterans) relative to small‐bodied, cold‐adapted taxa (e.g., chironomids and oligochaetes). Experimental warming consequently shifted assemblage size spectra in ways that were unexpected, but consistent with thermal optima of taxa in the regional species pool. Higher temperatures increased community‐level energy demand, which was presumably satisfied by higher primary production after warming. Our experiment demonstrates how warming reassembles communities within the constraints of energy supply via regional exchange of species that differ in thermal physiological traits. Similar responses will likely mediate impacts of anthropogenic warming on biodiversity and ecosystem function across all ecological communities. Abstract : Experimental whole‐stream warming altered invertebrate assemblage structure and decreased total invertebrate abundance by 60% relative to a reference stream, while invertebrate biomass was unchanged due to invasions of new taxa and increased proportions of large, warm‐adapted species relative to small‐bodied, cold‐adapted taxa. Community‐level energy demand increased due to higher temperatures and was presumably met by increased primary production during warming.